Perceived effects of ethnocentrism, offline and online interethnic interactions on interethnic bridging social capital among undergraduates in Malaysian public universities - Ketab, Somayeh Mortzavi Ganji (2015)
The development of interethnic bridging social capital in societies with ethnic diversity is quite challenging when ethnicity is considered as an obstacle. Individuals in Malaysian “ethnocratic state” may have their own exclusive ways of interpreting other ethnics. These attitudes may prevent them from effective interaction with people of different ethnic groups. Hence, examining the elements that strengthen or weaken interethnic bridging social capital is of importance in Malaysia. Therefore, this study was designed to explore the possible theoretical relationship between ethnocentrism (independent variable) and interethnic bridging social capital (dependent variable). This relationship was then mediated by interethnic interactions in both offline and online mode and moderated by ethnicity among undergraduate students in two Malaysian public universities. A self-administered questionnaire was employed to collect the data in this cross sectional survey. Sampling method used for the population of this study was stratified systematic sampling for 343 Malay, Chinese and Indian undergraduate students in Universiti Putra Malaysia and Universiti Kebangsaan Malaysia. Descriptive analysis,one-way Analysis of Variance, and Structural Equation Modeling were employed for data analysis. The results show that ethnocentrism has a significantly negative effect on interethnic bridging social capital among students. Ethnicity of the majority Malays and the minority Chinese negatively affected the relationship between ethnocentrism and interethnic bridging social capital, while this relationship was not moderated by minority Indians. Functioning as a mediator, offline and online interethnic interaction lessened the negative effect of ethnocentrism on interethnic bridging social capital. The results indicate that ethnocentrism predicts interethnic bridging social capital by explaining 16% of variance in the direct model. In addition, the 39% and 28% of the interethnic bridging social capital variances are explained by the offline and online frameworks respectively. Results reveal lower ethnocentrism among the students lead to higher interethnic bridging social capital. Both offline and online interethnic interactions were at moderate level, but the former was slightly higher than the latter. The Chinese and the Malays do not differ in their level of interethnic bridging social capital as well as offline interethnic interaction, but the Indians illustrates significantly higher interethnic bridging social capital and interethnic interaction. The Indians had the most online interethnic interaction, followed by the Chinese and the Malays. The main conclusion of this study is that Malaysia cannot be labeled as an ethnocentric society as claimed before. However, ethnicity is still a matter of consideration for Malaysian students to form their interethnic interaction, particularly in online realm. Comparison between two offline and online models reveals that the formation of weak ties among different ethnic groups in online space is more challenging than in the real world. Therefore, Malaysian government must take significant actions to strengthen online communication among various population groups. The present study contributed to the previous literature by filling the gap existed in interethnic bridging social capital studies in Malaysia. Moreover, the lack of literature about face-to-face as well as online interethnic interactions was fulfilled by the results of this study.